2021
DOI: 10.3390/biomedicines9081002
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Prevents T-Lymphocytes and Macrophages Infiltration in Cerebellum and Restores Motor Incoordination in Rats with Mild Liver Damage

Abstract: In patients with liver cirrhosis, minimal hepatic encephalopathy (MHE) is triggered by a shift in peripheral inflammation, promoting lymphocyte infiltration into the brain. Rifaximin improves neurological function in MHE by normalizing peripheral inflammation. Patients who died with steatohepatitis showed T-lymphocyte infiltration and neuroinflammation in the cerebellum, suggesting that MHE may already occur in these patients. The aims of this work were to assess, in a rat model of mild liver damage similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…We show here that CCL2 is increased in the hippocampus of rats with mild liver damage. Moreover, we previously showed that these rats have increased plasma levels of CX3CL1 at 4 weeks of CCl 4 treatment [ 36 ]. This suggest that the increased levels of CCL2 in the hippocampus and of CX3CL1 in blood of these rats would contribute to the infiltration of monocytes in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We show here that CCL2 is increased in the hippocampus of rats with mild liver damage. Moreover, we previously showed that these rats have increased plasma levels of CX3CL1 at 4 weeks of CCl 4 treatment [ 36 ]. This suggest that the increased levels of CCL2 in the hippocampus and of CX3CL1 in blood of these rats would contribute to the infiltration of monocytes in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Male Wistar rats (Charles River) weighing 150–180 g were intraperitoneally injected 3 times/week during 4 weeks with 1 mL/kg body weight of carbon tetrachloride (CCl 4 ) to induce liver damage. CCl 4 was prepared 1:10 ( v : v ) in corn oil as previously described [ 36 , 41 ] Control rats were intraperitoneally injected with corn oil. Rifaximin (Sigma, St. Louis, MO, USA) was dissolved in 100% ethanol and administered orally (20 mg/kg body weight).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the reagent could impose another therapeutic option for treating cerebellar inflammation. They also suggest that Rifampicin restored motor incoordination by peripheral inflammation in rats [228]. It is interesting that a tropical Southeast Asian fruit named noni (Morinda citrifolia L.) showed anti-inflammatory activity in microglial cells.…”
mentioning
confidence: 93%